1D and 2D Thiazole‐Based Copper(II) Coordination Polymers: Synthesis and Applications in Carbon Dioxide Capture. Issue 3 (21st January 2014) - Rossin, Andrea; Tuci, Giulia; Giambastiani, Giuliano; Peruzzini, Maurizio
Abstract The reaction of different copper(II) salts with a class of thiazole‐based ligands under solvothermal conditions produces three crystalline 1D/2D coordination polymers: [Cu(κ‐N‐thiazole)4(SiF6)]∞ (1 (1D)), Cu[μ‐(κ‐N:κ‐COO)‐L1]2⋅(H2O)∞ (2 (2D); HL1=2‐aminothiazole‐5‐carboxylic acid), and Cu[μ‐(κ‐N:κ‐COO)‐L2]2⋅1.5 (H2O)∞ (3 (2D); HL2=thiazole‐5‐carboxylic acid). All the materials have been characterized through common solid‐state techniques: single‐crystal (XRD) and (variable‐temperature) powder X‐ray diffraction (PXRD), infrared spectroscopy (IR), thermogravimetric analysis combined with mass spectrometry (TGA‐MS), and BET surface area and pore‐size distribution measurements. Polymer 3 shows a porous structure made of squared channels formed by the ordered stacking of the planar sheets along the a crystallographic axis (inner surface area equal to 15 m2 g−1, as inferred from N2 adsorption at T=77 K on the pre‐activated form), and it has been exploited for CO2 physisorption at ambient temperature (T=303 K) and pressure (p<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4ssg1mfv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> CO 2</alternatives> max.=920 torr). A remarkable CO2 uptake equal to 9.0 wt % was recorded under these mild conditions, thereby making the material promising for carbon dioxide capture in post‐combustion flue gas, in which the key factor for a successful performance is the high chemical selectivity for CO2 over N2.